2023
DOI: 10.1021/acs.est.3c00990
|View full text |Cite
|
Sign up to set email alerts
|

Microcystins-Loaded Aged Nanoplastics Provoke a Metabolic Shift in Human Liver Cells

Abstract: Studies concerning the toxicity of pollutant-loaded nanoplastics (NPs) toward humans are still in their infancy. Here, we evaluated the adsorption of microcystins (MCs) by pristine and aged polystyrene nanoplastics (PSNPs), prepared MCs-loaded aged PSNPS (1, 5, 10, 15, and 19 μg/mg), and systematically mapped the key molecular changes induced by aged and MCs-loaded PSNPs to human hepatoblastoma (HepG2) cells. According to the results, MC-LR adsorption is increased 2.64-fold by aging, and PSNP accumulation is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…More importantly, a few studies reported that the role of photoweathering enhanced the biotoxicity of contaminants. For example, photoaging reduced the size of microplastics (MPs), induced the production of nanoplastics (NPs), and promoted the leaching of chemical additives, which enhanced the hepatotoxicity of zebrafish . Meanwhile, NPs exhibited an increased capacity to adsorb more polar pollutants (e.g., microcystins) through surface oxidation, thus aggravating cytotoxicity . Our recent studies have also evidenced that photoaging induced the formation of environmentally persistent free radicals (EPFRs) in TWP, which are more reactive and induce oxidative stress and inflammatory response in in vitro cells. , At present, EPFRs, defined as a substance that carries unpaired electrons stably existing in natural conditions, have been considered an emerging contaminant with serious toxicity to human and ecological health. Overall, the photoweathering processes could influence the physicochemical characteristics (e.g., shape, size, surface chemistry, and additives) of TWP, resulting in inconsistent toxic responses by changing their interaction with organisms.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, a few studies reported that the role of photoweathering enhanced the biotoxicity of contaminants. For example, photoaging reduced the size of microplastics (MPs), induced the production of nanoplastics (NPs), and promoted the leaching of chemical additives, which enhanced the hepatotoxicity of zebrafish . Meanwhile, NPs exhibited an increased capacity to adsorb more polar pollutants (e.g., microcystins) through surface oxidation, thus aggravating cytotoxicity . Our recent studies have also evidenced that photoaging induced the formation of environmentally persistent free radicals (EPFRs) in TWP, which are more reactive and induce oxidative stress and inflammatory response in in vitro cells. , At present, EPFRs, defined as a substance that carries unpaired electrons stably existing in natural conditions, have been considered an emerging contaminant with serious toxicity to human and ecological health. Overall, the photoweathering processes could influence the physicochemical characteristics (e.g., shape, size, surface chemistry, and additives) of TWP, resulting in inconsistent toxic responses by changing their interaction with organisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, the percentage of MNPs, especially NPs, that are removed from the human body remains unclear. Due to their small sizes, NPs may be more hazardous than bigger plastic particles. , Furthermore, in vivo mammal and in vitro cell experiments showed that MNPs may cause intestinal disturbance, cardiovascular toxicity, reproductive toxicity, and acute mortality; however, their mechanisms remain unclear. It is also unknown whether MNPs produce the same effects on the human body. No direct evidence regarding this critical issue has yet been found yet.…”
Section: Introductionmentioning
confidence: 99%